Mediation System for cooperative activities: knowledge system design (2008)
In this article we present the use the knowledge for a Mediation System, developed to give support to mechanical system designer activities. The use of cooperative systems must contain a sufficient level of assistance to facilitate and coordinate the actor’s activities. To accomplish this goal we introduce an artificial actor: the Mediator. To illustrate our approach we will present the specification of the knowledge of the Mediation System.